Diagnostic accuracy of Bellavere’s score in cardiac autonomic neuropathy among chronic kidney disease patients: a study of prevalence and dialysis impact - Toshniwal, Saket Satyasham; Kumar, Sunil; Acharya, Sourya; Ghali, Abhishek; Raut, Sarang; Deolikar, Vinit; Reddy, Harshitha; Kotak, Palash; Wanjari, Anil; Bawankule, Shilpa (Frontiers in Medicine, 2025)
BackgroundCardiac autonomic neuropathy (CAN) is a significant complication in chronic kidney disease (CKD), leading to increased morbidity and mortality. Early detection is essential for managing CKD patients effectively, especially those on hemodialysis. This study evaluated the prevalence CAN in CKD and diagnostic accuracy of Bellavere’s Score in predicting CAN in CKD patients, including those undergoing hemodialysis.MethodsThis prospective observational study included 200 CKD patients. Cardiac autonomic neuropathy was assessed using Bellavere’s Score, calculated through a series of autonomic function tests including heart rate variability and blood pressure responses. Bellavere’s Score was measured pre-and post-dialysis in hemodialysis patients. The diagnostic performance of the score was evaluated using receiver operating characteristic (ROC) curves to determine sensitivity, specificity, and likelihood ratios.ResultsAmong the patients, 60% were diagnosed with CAN, with 35% having early CAN and 24% severe CAN. Bellavere’s Score showed high diagnostic accuracy across CKD stages, with sensitivity ranging from 75 to 89.29% and specificity from 69.09 to 96%. In CKD stage III patients, the sensitivity was 78.57% and specificity 91.4%. In stage V, sensitivity increased to 89.29%, though specificity dropped to 69.09%. For hemodialysis patients, Bellavere’s Score exhibited a sensitivity of 79.78% and specificity of 79.28%. The prevalence of CAN decreased significantly from 79.8% pre-dialysis to 64% post-dialysis (p < 0.01).ConclusionBellavere’s Score provides a reliable and non-invasive approach for diagnosing CAN in CKD patients, with strong diagnostic performance across different disease stages and in hemodialysis. Larger studies are warranted to further validate its utility.